2021
DOI: 10.3332/ecancer.2021.1267
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years’ experience of primary vaginal cancer treatment at one cancer centre: does residence status matter?

Abstract: Objectives: To study the long-term results of the treatment of patients with vaginal cancer and to examine whether there are any differences in diagnostic and survival rates between urban and rural patients. Methods:The data of 70 patients with primary vaginal cancer treated at NN Alexandrov National Cancer Centre of Belarus from 2000 to 2019 were included. The median age was 64 years (range = 56-75). Morphology in 91.4% (64/70) of the cases was squamous cell cancer, in 7.1% (5/70) it was adenocarcinoma and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…The survival outcomes from our study showed no discrepancies in survival between women living in urban and rural areas. This was also confirmed in our previous study of a single cancer center ( Matylevich et al, 2021 ). In our opinion, this is due to peculiarities of the health care system in Belarus, which is mostly provided through government-owned facilities, allowing citizens universal access to medical care, which is free at the point of use ( Richardson et al, 2013 ).…”
Section: Discussionsupporting
confidence: 89%
“…The survival outcomes from our study showed no discrepancies in survival between women living in urban and rural areas. This was also confirmed in our previous study of a single cancer center ( Matylevich et al, 2021 ). In our opinion, this is due to peculiarities of the health care system in Belarus, which is mostly provided through government-owned facilities, allowing citizens universal access to medical care, which is free at the point of use ( Richardson et al, 2013 ).…”
Section: Discussionsupporting
confidence: 89%